2011
DOI: 10.1109/tthz.2011.2161050
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Direct Detection in ${\hbox{YBa}}_{2}{\hbox{Cu}}_{3}{\hbox{O}}_{7}$ Microbolometers

Abstract: A high sensitivity broadband terahertz direct detector based on YBa 2 Cu 3 O 7 high-Tc superconductor microbolometers is presented. At 77 K, the responsivity of the spiral antenna-integrated microbolometers (1.5 μm x 1.5 μm) is 190 V/W, referenced to the input of the silicon substrate lens, across the frequency range of 330 GHz to 1.63 THz in a single device. The response time is approximately 300 ps. Using a room temperature readout, we measure an optical noise equivalent power (NEP) of 20 pW/Hz 1/2 (readout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…For large bias currents, the R v (i) deviates from a linear function, because the denominator in (2) starts to decrease. A nearly constant responsivity from 300GHz to 1.6THz for the discussed YBCO bolometers was reported in [11] for an operation temperature of 77K. At room temperature, the bolometers are expected to have similar RF bandwidth that is limited by the antenna.…”
Section: Responsivity Measurementsmentioning
confidence: 67%
See 2 more Smart Citations
“…For large bias currents, the R v (i) deviates from a linear function, because the denominator in (2) starts to decrease. A nearly constant responsivity from 300GHz to 1.6THz for the discussed YBCO bolometers was reported in [11] for an operation temperature of 77K. At room temperature, the bolometers are expected to have similar RF bandwidth that is limited by the antenna.…”
Section: Responsivity Measurementsmentioning
confidence: 67%
“…A Teflon lens focused the beam on the Si lens/bolometer. The optical coupling efficiency to the spiral antenna bolometers on a silicon lens has been discussed in [11]: ∼4-5dB, that accounted for the Si lens reflection losses, polarization losses, and beam coupling losses. In this paper, THz power, absorbed in the bolometer, was used for the responsivity calculation.…”
Section: Experimental Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Response time of diffusion-cooled type bolometers has been presented by Prober (1993). YBCO high temperature superconducting thin film based microbolometer for THz radiation was demonstrated and response time of 300 ps was achieved (Hammar et al 2011). In addition to these, antenna structures were fabricated to provide higher sensitivity from the detectors (Mendis et al 2004;Hosseini et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…By using high temperature superconductor YBa 2-Cu 3 O 7-x (YBCO) thin film for the production of the bolometer, Hammar et al acquired response times almost at the range of picoseconds. Moreover, they demonstrated that responsivity is decreased when increasing the antenna structure which 1.5 lm 9 1.5 lm area has nearly 180 V/W and 4 lm 9 1 lm area has 100 V/W as responsivity (Hammar et al 2011). MgB HEBs operating at THz frequency which are produced from 20 nm films on silicon substrates has been achieved as well (Cherednichenko et al 2007).…”
Section: Introductionmentioning
confidence: 99%